The Role of Village Governments in Reducing the Risk of Flood Disaster Through Disaster Preparedness Villages - Kurnia Dwi Anggraini; Isna Fitria Agustina (Indonesian Journal of Cultural and Community Development, 2021)
This study aims to identify and describe the role of the village government in reducing flood risk through the Disaster Alert Village in Kademangan Village, Mojoagung Jombang. The type of research is descriptive qualitative research. Data collection techniques using observation techniques, interviews, and documentation. The technique of determining the informant uses a purpose sampling technique. Data analysis was carried out using data reduction techniques, data presentation, and drawing conclusions. The results showed that the role of the Kademangan village government in reducing flood risk through the Disaster Alert Village, namely: the government's role as a regulator by making regulations to reduce flood risk in Kademangan village by forming an organization Disaster Alert Village. The government's role as a dynamizer is a driving force to move the community to participate in overcoming problems or obstacles that occur by realizing the success of the goals to be achieved. The role of the government as a facilitator is to provide facilities for communities affected by floods.